Dicarboxylic acids in the Arctic aerosols and snowpacks collected during ALERT 2000 - Narukawa, M.; Kawamura, K.; Li, S. M.; Bottenheim, J. W. (ATMOSPHERIC ENVIRONMENT, 2002)
Saturated (C(2)-C(11)) and unsaturated (C(4)-C(5), C(8)) dicarboxylic acids were measured in Arctic aerosol and surface snowpack samples collected during dark winter (February) and light spring (April-May) using a gas chromatography and gas chromatography/mass spectrometry. Their molecular distributions were characterized by a predominance of oxalic acid (C(2)), except for few spring snowpack samples that showed the predominance of succinic acid (C(4)). Concentrations of short-chain saturated diacids (C(3)-C(5)) and 4-ketopimelic acid in the aerosol samples increased by a factor of similar to5 from winter to spring. In contrast, those of saturated C(6)-C(11) diacids and unsaturated (maleic, methylmaleic and phthalic) acids decreased by a factor of similar to4 from winter to spring aerosol samples. Snowpack samples also showed a similar trend. These results of the aerosol samples suggested that, the diacids are largely produced in spring by photochemical oxidation of hydrocarbons and other precursors that are transported long distances from the mid- and low-latitudes to the Arctic, but the production of oxalic acid is in part counteracted by photo-induced degradation possibly associated with bromine chemistry. (C) 2002 Elsevier Science Ltd. All rights reserved.